Identifikasi Cendawan Entomopatogen Dari Rizosfer Tanaman Kelapa Sawit (Elaeis guineensis J.) - S, Nur Khalifah; Pramudi, Muhammad Indar; Soedijo, Samharinto (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Entomopathogens are microorganisms that can cause disease in insects. Entomopathogenic fungi are one type of bioinsecticide that can kill insects by infecting them through the skin, digestive tract, spiracles and other holes. This research aims to identify entomopathogenic fungi from around oil palm plants. The method used in this research began with a survey and purposive sampling of soil samples taken at the oil palm plantation of PT Mulia Agro Permai Timur Sampit, Central Kalimantan. Samples were taken at five different points, one sample was obtained at each point at a depth of 15-20 cm. From the isolation results, five types of isolates were obtained, namely the fungi Penicillium spp., Mucor spp., Trichoderma spp., Metarhizium spp., and Beauveria spp. From the Koch Postulate test using Hong Kong caterpillar larvae (Tenebrio molitor) as test larvae which were inoculated with entomopathogenic fungi. The results showed that the five fungus isolates were able to cause death in the test larvae with different death times for each isolate.